Prevalence of metabolic syndrome and its components in patients with arterial hypertension and obesity - I. E. Chazova; V. B. Mychka; T. N. Erivantseva; S. P. Olimpieva; V. V. Kilikovsky (Кардиоваскулярная терапия и профилактика, 2005)
Aim. To compare prevalence of metabolic syndrome (MS) by WHO and ATP III criteria, in patients with arterial hypertension (AH) and obesity. Material and methods. MS prevalence in obese AH patients was studied in 517 males and 1041 females aged 20- 75 years. Two most well-known definitions of MS, proposed by World Health Organization (WHO) and National Cholesterol Education Program’s Adults Treatment Panel III, National Institutes of Health, USA (ATP III, USA) were used. Results. Among 1558 participants, MS was diagnosed in 72% by ATP III criteria, and in 17% by WHO criteria. MS prevalence was gender-specific: in males, it was 62% (ATP III) or 19% (WHO), in females - 76% or 16%, respectively. MS diagnostic agreement was observed in 44% of the participants: MS was diagnosed by both definitions in 16%, and not diagnosed by both definitions in 28%. 58% of the patients had MS verified by only one diagnostic version. Conclusion. For wider use in clinical practice, unified MS definition should be created, or methods integrating different diagnostic criteria, should be introduced.